2019
DOI: 10.1159/000500490
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of a Genetic Risk Score for Obesity and Related Traits among Chinese Patients with Type 2 Diabetes

Abstract: Background: Obesity is more prevalent in men than in women in China, especially within the middle-aged population. Objectives: The present study aims to determine the contribution of sexual dimorphisms to obesity and related traits in terms of the mechanisms involving the obesity-related genetic variants among patients of Chinese Han ancestry with type 2 diabetes. Method: In the Chinese National Diabetes and Metabolic Disorders Study, 2,555 out of 4,036 patients with type 2 diabetes were treatment naive, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Clearly, the frequency of the C allele is higher in the T2DM group (0.99) than in the control group (0.88). We found a strong association of MC4R rs2229616 variant with T2DM risk similar to the results from a study of patients of Chinese Han ancestry with T2DM [53]. No study on this MC4R SNP had been conducted on T2DM patients in the Arab populations.…”
Section: Discussionsupporting
confidence: 84%
“…Clearly, the frequency of the C allele is higher in the T2DM group (0.99) than in the control group (0.88). We found a strong association of MC4R rs2229616 variant with T2DM risk similar to the results from a study of patients of Chinese Han ancestry with T2DM [53]. No study on this MC4R SNP had been conducted on T2DM patients in the Arab populations.…”
Section: Discussionsupporting
confidence: 84%
“…Based on genome-wide association analysis data, genetic variants in FTO and TFAP2B , previously known as obesity susceptibility loci, impinge independently on the risk of metabolic syndrome [ 31 ]. Studies from Asia have revealed that genetic predisposition to the FTO and TFAP2B genes contributed to a sex-dependent pattern of obesity-related traits and remarkable accumulation of abdominal fat [ 32 , 33 ]. The transcription factor TFAP2B is involved in regulating adipocyte metabolism by stimulating glucose uptake and lipid accumulation while decreasing insulin sensitivity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the lack of significant association between 2D : 4D and adult circulating testosterone may be that Leydig cells (responsible for testosterone production in There is an association between estrogen levels and fasting lipid parameters in adults according to previous studies. Premenopausal women are said to have better lipid homeostasis with a less proatherogenic lipid profile than men although there are ethnic, genetic, and environmental variabilities [35][36][37][38]. Although the sex difference is not clearly understood, HDL-C tends to be higher while LDL-C, VLDL-C, and triglycerides levels are lower in premenopausal women than in age-matched men and this has been attributed to the activities of estrogen [2].…”
Section: Discussionmentioning
confidence: 99%